Genomic Applications in Pathology (Springer New York, 2015)
Genomic Applications in Pathology provides a state-of-the art review of the scientific principles underlying next generation genomic technologies and the required bioinformatics approaches to analyses of the daunting amount of data generated by current and emerging genomic technologies. Implementation roadmaps for various clinical assays such as single gene, gene panels, whole exome and whole genome assays are discussed together with issues related to reporting, including the pathologist's role in interpretation and clinical integration of genomic tests results. Genomic applications for site-specific solid tumors and hematologic neoplasms are detailed, as well as genomic applications in pharmacogenomics, inherited genetic diseases, and infectious diseases. The latest iteration of practice recommendations and guidelines in genomic testing, put forth by stakeholder professional organizations such as the Association for Molecular Pathology  and the College of American Pathologists, are also discussed in the volume, as well as regulatory issues and laboratory accreditation related to genomic testing. Written by experts in the field, Genomic Applications in Pathology provides a comprehensive resource that is of great value to practicing molecular pathologists, hematopathologists, other subspecialized pathologists, general pathologists, pathology trainees, oncologists, and geneticists